2019
DOI: 10.2147/cmar.s190510
|View full text |Cite
|
Sign up to set email alerts
|

<p>Meta-analysis of the prognostic value of C-C chemokine receptor type 7 in patients with solid tumors</p>

Abstract: Background Expression of C-C chemokine receptor type 7 (CCR7) is associated with the prognosis of several cancers. The aim of this study was to conduct the meta-analysis to determine the prognostic value of CCR7 expression in solid tumors. Materials and methods We searched for relevant literature in the PubMed, Embase, and Cochrane Library databases (last updated on January 15, 2018). The associations of CCR7 expression with overall survival (OS), disease-free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…CCR7 has also been found to induce EMT in PDAC and lung cancer (LC) [174,175], promote MMP-2 and -9 expression in bladder cancer [176], and facilitate tumor cell dissemination, migration, and eventually metastasis formation [177]. With the strong protumor functions, the expression of CCR7 or CCL21 has been reported to be strongly correlated with poor survival [169,178]. Hence, CCR7 could become a predictive marker for a number of cancers, including colorectal liver metastasis.…”
Section: Ccr7mentioning
confidence: 99%
“…CCR7 has also been found to induce EMT in PDAC and lung cancer (LC) [174,175], promote MMP-2 and -9 expression in bladder cancer [176], and facilitate tumor cell dissemination, migration, and eventually metastasis formation [177]. With the strong protumor functions, the expression of CCR7 or CCL21 has been reported to be strongly correlated with poor survival [169,178]. Hence, CCR7 could become a predictive marker for a number of cancers, including colorectal liver metastasis.…”
Section: Ccr7mentioning
confidence: 99%
“…As described above, aberrant expression of CCR7 is observed in several cancers and this expression often corelates with poor prognosis. A meta-analysis of published literature up to January 2018 has shown that higher expression of CCR7 correlates with poorer overall survival (OS) and progression-free survival (PFS), although it did not show any correlation with disease-free survival (DFS), and recurrence-free survival (RFS) [208]. This is of course not surprising since CCR7 expression correlates with LN metastasis which in itself is an indicator of poor prognosis.…”
Section: Ccr7/ccl19/ccl21 As a Prognostic Biomarker In Cancermentioning
confidence: 99%
“…First, in this retrospective study, samples were collected from a single Japanese center. Notably, a meta-analysis reported that the impact of high CCR7 expression on poor OS was more significant in Asian patients than that in Caucasians [ 38 ]. Therefore, a larger and more diverse sample must be analyzed to eliminate the risk of bias and validate the conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%